IMPLEMENTASI KEBIJAKAN PENCEGAHAN NARKOBA MELALUI PROGRAM KELURAHAN BERSIH DARI NARKOBA (BERSINAR) DI KELURAHAN SETU - Luthfi Fathurrahman; Sokhivah (Journal of Research and Publication Innovation, 2024)
The distribution of drugs has entered the warning zone in the South Tangerang City area, one of which is in Setu Village. This has the potential to increase the number of drug abuse in Setu Village. This research aims to find out the implementation of the Drug Abuse Prevention Program Policy in Setu Village as well as supporting and inhibiting factors. The Program Implementation approach uses theory according to Edward III (1980), namely the Communication, Resources, Disposition and Bureaucratic Structure approach. This field research uses qualitative research. The technique for collecting informants uses the Snow Ball Technique. As well as data collection obtained from the results of interviews, observations and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The location of this research is in Setu Village, Setu District, South Tangerang City. The results of the research show that the main problem in the implementation of Drug-Free Villages in Setu Village is still the lack of anti-drug volunteers. Then the achievement was the formation of a Volunteer Agent and Recovery Agent in the Setu sub-district whose members consisted of local people, both youth and community leaders. These volunteers will help the sub-district government to socialize and carry out supervision and control for those suspected of being involved in the activities of consuming or distributing illegal drugs (narcotics). Supporting factors for the implementation of the Bersinar Village Program Policy are the support from the City Government and the South Tangerang City BNN, which has provided facilities such as a secretariat, budget funding sources provided by the BNN. And the inhibiting factor is the lack of volunteers in implementing the program in the Setu sub-district which can be an obstacle in implementing the drug-free sub-district program.